2016
DOI: 10.22211/cejem/64994
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Impact Sensitivity of Nitroaromatic Energetic Compounds and their Electrostatic Sensitivity

Abstract: This study presents a linear relationship between the impact sensitivity of nitroaromatic energetic compounds and their electric spark sensitivity. The methodology assumes that the impact sensitivity of a nitroaromatic energetic compound with the general formula CaHbNcOd can be expressed as a function of the electrostatic sensitivity, the number of NH2 group substitutions in the 2,4,6-trinitrophenyl ring and non-additive structural parameters. The root mean square and absolute standard deviation of a newly int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…According to Equation (2), the primary fragmentation reactions of energetic compounds by electric spark and impact have the same trend except for some compounds in which the presence of some molecular fragments may provide large deviations. Thus, the same as previous studies for the selected classes of energetic compounds,[14a], [14b] Equation (2) can provide a general pathway to correlate mechanism of energy transfer of an energetic compound from electric spark or impact to the reaction center of a molecule. The experimental values of impact sensitivities depend on shape and size of crystals that might connect with dislocations in these crystals.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Equation (2), the primary fragmentation reactions of energetic compounds by electric spark and impact have the same trend except for some compounds in which the presence of some molecular fragments may provide large deviations. Thus, the same as previous studies for the selected classes of energetic compounds,[14a], [14b] Equation (2) can provide a general pathway to correlate mechanism of energy transfer of an energetic compound from electric spark or impact to the reaction center of a molecule. The experimental values of impact sensitivities depend on shape and size of crystals that might connect with dislocations in these crystals.…”
Section: Resultsmentioning
confidence: 95%
“…Some investigations have been done to correlate electric spark sensitivity with the other types of sensitivity for some classes of energetic compounds. [3a], …”
Section: Resultsmentioning
confidence: 99%
“…The elemental compositions of different classes of energetic compounds are important parameters for assessment of their impact sensitivities [5][6][7][8][9][10][17][18][19][20]. For ionic liquids, it has been found that the elemental composition and the contributions of some cations or anions are important for the assessment of some properties such as density [21,22].…”
Section: Development Of the New Modelsmentioning
confidence: 99%
“…These data have been used in recent years for the development of predictive methods for nitramines [14][15][16][17][18][19] and polynitroarenes [20][21][22]. Furthermore, the reported electric spark sensitivities based on the output from RDAD instruments have also been correlated with detonation performance [12,[23][24][25][26], impact sensitivity [27,28], thermal stability [29][30][31][32][33], and shock sensitivity [34,35]. Most of the available predictive methods and the new computer code EMDB [36] for the prediction of electric spark sensitivity are based on data reported for the old RDAD instrument.…”
Section: Introductionmentioning
confidence: 99%